Ecoanalytical Monitoring of Natural Objects and the Role of Physico-Chemical Analysis in It (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Protection of environment and nature is one of the main problems of today. In recent years, as a result of the construction of many industrial enterprises in densely populated countries, cities, and districts, and as a result of the increase in the number of technical means considered necessary for the needs of the population, the air of cities is becoming polluted, and the amount of harmful gases in it is increasing.